2008
DOI: 10.1021/jf801731n
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Peanut (Arachis hypogaea, Leguminosae) Proteins by Activated Charcoal

Abstract: The binding of peanut protein allergens to activated charcoal (AC), used medically for gastric decontamination following the ingestion of toxic substances, was investigated for potential clinical application. Crude peanut extract (CPE) or purified peanut protein allergens Ara h 1 and 2 were co-incubated with AC under a variety of conditions followed by centrifugation to remove the AC and adsorbed protein. The resulting supernatant solution was analyzed for unadsorbed protein by gel electrophoresis and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
2
4
1
Order By: Relevance
“…The exclusion of large molecules from portions of the activated carbon’s internal surfaces should allow it to selectively remove smaller proteins from larger proteins if the pores are of a sufficient size. This conclusion is consistent with an investigation by Kopper et al into the purification of peanut proteins, which found that when activated carbon was saturated with a large protein, it still retained its binding capacity for a smaller protein . However, it is difficult to make definitive conclusions on how a protein’s size influences its adsorption on activated carbon by examining proteins of varying size, since they will also differ in their charge, shape, and hydrophobicity.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…The exclusion of large molecules from portions of the activated carbon’s internal surfaces should allow it to selectively remove smaller proteins from larger proteins if the pores are of a sufficient size. This conclusion is consistent with an investigation by Kopper et al into the purification of peanut proteins, which found that when activated carbon was saturated with a large protein, it still retained its binding capacity for a smaller protein . However, it is difficult to make definitive conclusions on how a protein’s size influences its adsorption on activated carbon by examining proteins of varying size, since they will also differ in their charge, shape, and hydrophobicity.…”
Section: Introductionsupporting
confidence: 86%
“…This conclusion is consistent with an investigation by Kopper et al into the purification of peanut proteins, which found that when activated carbon was saturated with a large protein, it still retained its binding capacity for a smaller protein. 12 However, it is difficult to make definitive conclusions on how a protein's size influences its adsorption on activated carbon by examining proteins of varying size, since they will also differ in their charge, shape, and hydrophobicity. Previous studies of activated carbon with polymers are instructive since polymers do not differ in their chemical characteristics as a function of size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure indicates that peanut proteins are adsorbed with equal efficiency at pH 2 and 7 and are completely removed from solution by an AC/protein ratio of approximately 80:1. These findings corroborate our previously published results using a peanut protein mixture prepared from defatted peanut flour . This suggests that AC could quantitatively adsorb soluble allergenic peanut protein whether encountered in the stomach (pH 2) or intestine (pH 7).…”
Section: Discussionsupporting
confidence: 92%
“…They found that AC removed IgE-binding peanut proteins from solution in vitro and suggested that it may be useful as an adjunct to the present standard management of peanut anaphylaxis. However, these studies were performed under nonphysiological conditions that have subsequently been shown to significantly affect the amount of AC required for complete adsorption of soluble protein (20). There have as yet been no studies of protein adsorption by AC under actual physiological conditions in vivo.…”
Section: Introductionmentioning
confidence: 99%